Current trends in partial adrenalectomy. Issue 2 (March 2015) - Colleselli, Daniela; Janetschek, Günter
Abstract : Purpose of review: Total adrenalectomy has been the standard treatment for small adrenal masses for years. In recent times, however, partial adrenalectomy and cortex-preserving strategies are gaining more importance. Therefore, we evaluated indications, techniques and outcome of partial adrenalectomy. Recent findings: With more small adrenal masses identified through the widespread use of imaging modalities, partial adrenalectomy and cortical-preserving strategies were applied in various indications and techniques. In all original papers published on this topic during the review period of the last 18 months, minimal invasive approaches were used with satisfying surgical and functional outcomes. Summary: There is a definitive trend towards the use of partial adrenalectomy in the treatment of small adrenal masses. In bilateral disease, steroid replacement can be avoided in most cases, whereas successful normalization of pathological endocrine levels was reported in various indications. Therefore, minimal invasive partial adrenalectomy may become the recommended standard treatment of small benign and hormonal active adrenal tumours.